Efek Mediasi Brand Trust dalam Pengaruh Brand Image dan E–Service Quality Terhadap Customer Loyalty Bukalapak - Affandi, Muhammad; Suherman, Suherman; Aditya, Shandy (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
The purpose of this study was to determine the effect of brand trust mediation in the influence of brand image and e–service quality on customer loyalty Bukalapak. The population in this study are Bukalapak users who are domiciled in DKI Jakarta, aged 17 years and over, and have transacted in Bukalapak at least 3 times in the last 1 month. The sample in this study was 150 people using purposive sampling method. Data analysis is done with the help of a computer application program that is Smart PLS. The result of this study showed that 1) brand image has a positive and significant effect on customer loyalty, 2) e-service quality has a positive and significant effect on customer loyalty, 3) brand image has a positive and significant effect on Brand Trust, 4) e-service quality has a positive and significant effect on brand trust, 5) brand trust has a positive and significant effect on customer loyalty, 6) brand trust mediates the positive and significant influence of brand image on customer loyalty, 7) brand trust mediates the positive and significant influence of e-service quality on customer loyalty. The conclusion in this study is customer loyalty is strongly influenced by brand image and e-service quality through brand trust. The higher brand image and e-service quality of a company, it will cause brand trust in consumers, and ultimately the more consumers trust a company, it will cause customer loyalty.